(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aims to investigate the hepatoprotective, anti-inflammatory, and wound-healing potentials of spirulina utilizing a rat model. Materials and Methods: Carbon tetrachloride (CCl4) was used to induce hepatotoxicity, while carrageenan was employed to induce hind paw inflammation. The wound healing capability was assessed by making a 6 mm round wound with a biopsy punch on the dorsal interscapular area of each rat. The animals were fed a diet mixed with spirulina at dosages of 250 and 500 mg.kg−1bwt. Paw thickness measurements were taken at 1, 3, and 6 h after carrageenan injection. Results: Intraperitoneal injection of CCl4 leads to hepatotoxicity, as evidenced by significantly elevated serum levels of alanine aminotransferase and aspartate aminotransferase. Treatment with spirulina markedly reduced these biochemical markers. CCl4 -induced hepatic cellular necrosis, central vein congestion, and steatosis were notably improved following spirulina administration. Additionally, spirulina treatment diminished paw edema and shortened wound closure time in a dose-dependent manner. Histopathological analysis of the inflamed paw revealed massive infiltration of inflammatory cells and thickening of the epidermis, both of which showed significant improvement with spirulina treatment. The anti-inflammatory and wound-healing effects of spirulina were comparable to those of indomethacin, an established anti-inflammatory drug. Conclusion: Our findings demonstrate that Spirulina platensis possesses beneficial properties in counteracting hepatotoxicity and inflammation. Additionally, it exhibited significant wound-healing effects in rat models. These results reinforce the potential health advantages of spirulina as an effective functional food. J. Adv. Vet. Anim. Res., 12(1): 303–311, March 2025 http://doi.org/10.5455/javar.2025.l897